Low-Intensity Transcranial Ultrasound Stimulation Promotes Recovery in Blood Flow and Movement Following Prolonged Anesthesia - Hang Song; Yinuo Zeng; Liyuan Ren; Huan Zhang; Aitao Wang; Junfeng Sun; Shanbao Tong (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
General anesthesia is a routine operation before surgical and diagnostic procedures. However, delayed emergence from anesthesia can lead to various complications. Researchers have sought to use transcranial ultrasound stimulation to promote motor and cognitive function recovery after short-period anesthesia (<60 min). However, whether the significant decline of neurovascular activities induced by prolonged anesthesia (>90 min) would affect ultrasound-induced recovery remains unclear. In this study, we investigated the effects of ultrasound stimulation on the recovery of mice after prolonged anesthesia by analyzing the changes of cortical blood flow and movement. C57BL/6 mice (n =24) were randomly assigned to the three groups: Control, Sham, and Ultrasound Stimulation. We utilized laser speckle contrast imaging to record cortical blood flow during and after 120 min anesthesia. Additionally, we recorded the emergence time of the first and full movements as indicators of recovery. The results showed that ultrasound stimulation significantly accelerated the recovery of blood flow (F(2,21) =3.83, p =0.038, $η _{p}^{{2}} =0.267$ ) and reduced the emergence time of the first movement (F(2,21) =2.70, p =0.091, $η _{p}^{{2}} =0.205$ ) after 120 min anesthesia. Furthermore, we observed a medium negative correlation between the blood flow after 120 min anesthesia and the emergence time of the first movement (r(22) $= -0.487$ , p =0.016, 95% CI: [−0.744,−0.104]). These findings revealed the potential of ultrasound stimulation to facilitate recovery after prolonged anesthesia.